Beliefs of primary school teachers on ESL students’ success - Kartar Singh, Kulwant Kaur; Yamat, Hamidah; Kartar Singh, Jaswir Kaur (Unit Penerbitan IPG KPM, 2017)
The purpose of this research is to discover the beliefs of primary school teachers pertaining to issues involving ESL students’ success and pedagogy in the ESL classroom. This study uncovered the factors that the teachers believed affect students’ mastery of the English language in Malaysia. The data was retrieved through interviews from three ESL teachers with different years of experience and they were categorised as veteran, experienced and novice teacher. Qualitative data analysis software, ATLAS.ti Version 7 was used to yield the teachers’ beliefs about factors contributing to students’ success in the ESL classroom through constant comparative and thematic analysis. The findings revealed that the role of teachers, students’ attitude, family and peers are the factors that are significant in determining the success of students. This implies that there is a need for collaboration to encourage learning and using the English language effectively to enhance the pedagogy and thinking skills.